Carbon disclosure practices of Aerospace and Airlines companies: substantive or symbolic legitimation / Faisal Faisal, Hasna Azizah Fithriani and Tarmizi Achmad - Faisal, Faisal; Fithriani, Hasna Azizah; Achmad, Tarmizi (Universiti Teknologi MARA Cawangan Sarawak, 2016)
This study investigates whether firms increase their carbon disclosure to gain the attention of stakeholder and whether the pattern of disclosure is symbolic or substantive. Content analysis of the annual and sustainability reports of forty-two aerospace, air courier and airlines companies listed on Forbes 2000 was conducted to measure and compare disclosure practices in 2011 and 2013. The descriptive statistics and Wilcoxon signed-rank test were carried out to answer the research questions. We found that firms do increase their carbon disclosure in sustainability reports only. In spite of the fact that previous studies have generally stated that disclosures have been used by corporations as a tool to legitimize their actions, the results of our study differ slightly. A more carbon-intensive industry such as aerospace, air courier and airlines has disclosed substantive information in relation to carbon. This study suggests that stronger requirements from regulators such as compliance obligations to disclose substantive information are most likely to make firms more accountable in their carbon disclosures. This result indicates that companies from this industry have made a substantial commitment to carbon reduction. This finding supports decision-makers, in particular regulators, to continue to institutionalize carbon regulation. It also provides empirical evidence of patterns of carbon disclosure in a specific industry.